2018
DOI: 10.31234/osf.io/j9ae5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Twenty years of stereotype threat research: A review of psychological mediators.

Abstract: This systematic literature review appraises critically the mediating variables of stereotypethreat. A bibliographic search was conducted across electronic databases between 1995and 2015. The search identified 45 experiments from 38 articles and 17 unique proposedmediators that were categorized into affective/subjective (n = 6), cognitive (n = 7) and motivationalmechanisms (n = 4). Empirical support was accrued for mediators such as anxiety,negative thinking, and mind-wandering, which are suggested to co-opt wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 68 publications
2
94
0
1
Order By: Relevance
“…Given that a growing awareness of racism is part of normative development (Garcia Coll et al, 1996), other scholars have investigated interventions for actively disrupting stereotype threat (e.g., Pennington, Heim, Levy, & Larkin, 2016;Taylor & Walton, 2011). A number of these studies have found that encouraging adolescents to either access an alternative, non-stereotyped identity or affirm their identity in order to restore a positive self-image can help mitigate the impact of stereotype threat (Croizet, D esert, Dutr evis, & Leyens, 2001;Taylor & Walton, 2011).…”
Section: Stereotype Threatmentioning
confidence: 99%
“…Given that a growing awareness of racism is part of normative development (Garcia Coll et al, 1996), other scholars have investigated interventions for actively disrupting stereotype threat (e.g., Pennington, Heim, Levy, & Larkin, 2016;Taylor & Walton, 2011). A number of these studies have found that encouraging adolescents to either access an alternative, non-stereotyped identity or affirm their identity in order to restore a positive self-image can help mitigate the impact of stereotype threat (Croizet, D esert, Dutr evis, & Leyens, 2001;Taylor & Walton, 2011).…”
Section: Stereotype Threatmentioning
confidence: 99%
“…Finally, although research has established a number of mediators of stereotype threat effects (for a review see Pennington, Heim, Levy, & Larkin, 2016), we did not examine any process variables in the current studies. In the review of Pennington et al (2016), the mediators of stereotype threat are grouped into three broad categories: affective/subjective (e.g., anxiety), cognitive (e.g., working memory), and motivational (e.g., effort). The mediators of stereotype threat effects are likely to depend on whether the outcome is performance or disengagement.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Stereotype threat, one of the most widely investigated topics in social psychology (Pennington et al 2016) occurs when underachievement among stigmatized group members is rooted in the situation more than in the individual (Leyens et al 2000).…”
Section: The Social Context Of Neuropsychological Assessment In Ageingmentioning
confidence: 99%
“…In particular, increased levels of anxiety have been offered to mediate the effects of stereotype threat on performance. However, results regarding this hypothesis have been mixed (see a review by Pennington et al 2016), with several studies failing to establish this relationship (e.g., Spencer et al 1999). Therefore, while anxiety may play a role in explaining stereotype threat effects (especially when assessed via indirect measures, Bosson et al 2004), it is likely not the only or the key explanation.…”
Section: Understanding Stereotype Threat Effectsmentioning
confidence: 99%